Stage of Quality Development of Accounting in New Uzbekistan - Samiddin Tashnazarov; Bonu Davronova (Researchparks Publishing, 2022)
This article describes the work done and strategic tasks in the qualitative development of accounting in the new Uzbekistan. It offers suggestions for improving the regulatory framework for accounting.